Soft Tissue Structures at Risk With Percutaneous Posterior to Anterior Screw Fixation of the Talar Neck. (October 2018) - Roberts, Lauren E.; Pinto, Martim; Staggers, Jackson R.; Godoy-Santos, Alexandre; Shah, Ashish; de Cesar Netto, Cesar
Background: Fractures of the talar neck and body can be fixed with percutaneously placed screws directed from anterior to posterior or posterior to anterior. The latter has been found to be biomechanically and anatomically superior. Percutaneous guidewire and screw placement poses anatomic risks for posterolateral and posteromedial neurovascular and tendinous structures. The objective of this study was to determine the injury rate to local neurovascular and tendinous structures using this technique in a cadaveric model. In addition, we aimed to determine the number of attempts at passing the guidewires required to achieve acceptable placement of 2 parallel screws. Methods: Eleven fresh frozen cadaver limbs were used. Two 2.0-mm guidewires were placed under fluoroscopic guidance, posterior to anterior centered within the talus. The number of attempts required was recorded. A layered dissection was then performed to identify injury to any local anatomic structure. The shortest distance between the closest guidewire and the soft tissue structures was measured. Results: The mean total number of guidewires passed to obtain optimal placement of 2 parallel screws was 2.9 ± 0.7. Direct contact between the guidewire and the sural nerve was seen in 100% of the specimens, with the nerve impaled by the guidewire in 3 of 11 (27.2%) cases. The peroneal tendons were impaled in 1 of 11 (9%) specimens and the Achilles tendon was in contact with the guidewire in 8 of the 11 (72.7%) specimens, and impaled at its most lateral border with the guidewire in 2 specimens (18.2%). Conclusion: The placement of posterior to anterior percutaneous screws for talar neck fixation is technically demanding, and multiple guidewires are needed. Our cadaveric study showed that important tendinous and neurovascular structures were in proximity with the guidewires and that the sural nerve was injured in 100% of the cases. Clinical Relevance: Given the risk of injury to these structures, we recommend a formal posterolateral incision for proper visualization and retraction of the anatomic structures at risk.